Mali : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2013)
Mali's territorial integrity is threatened, questioning its internal capacity to face challenges and especially to ensure the physical safety of goods and individuals. The government is committed to implement all measures to overcome this situation. More specifically, it will increase political and diplomatic actions for a quick and successful crisis outcome, maintain peace and security, revive economic activity, maintain social gains and target the poorest populations, fight against corruption and financial crime, and improve revenue mobilization to reduce dependence on aid.